Pride and perseverance [videorecording (DVD)] : the story of the Negro Leagues - Scott, Jeff; Winfield, Dave, 1951- (A+E Networks, 2014)
The history of the Negro Leagues is often a forgotten part of baseball history, and despite its popularity and wealth of talent was not well documented. The film sheds light on this period and shows how it laid the groundwork for today's African-American players in Major League Baseball. Includes footage from the 1920 through the 1950s.